Revision and phylogenetic analysis of the orb-weaving spider genus Glenognatha Simon, 1887 (Araneae, Tetragnathidae) - Cabra-García, Jimmy; Brescovit, Antonio D. (Zootaxa, 2016)
A taxonomic revision and phylogenetic analysis of the spider genus Glenognatha Simon, 1887 is presented. This analysis is based on a data set including 24 Glenognatha species plus eight outgroups representing three related tetragnathine genera and one metaine as the root. These taxa were scored for 78 morphological characters. Parsimony was used as the optimality criterion and a sensitivity analysis was performed using different character weighting concavities. Seven unambiguous synapomorphies support the monophyly of Glenognatha. Some internal clades within the genus are well-supported and its relationships are discussed. Glenognatha as recovered includes 27 species, four of them only known from males. A species identification key and distribution maps are provided for all. New morphological data are also presented for thirteen previously described species. Glenognatha has a broad distribution occupying the Neartic, Afrotropic, Indo-Malaya, Oceania and Paleartic regions, but is more diverse in the Neotropics. The following eleven new species are described: G. vivianae n. sp., G. caaguara n. sp., G. boraceia n. sp. and G. timbira n. sp. from southeast Brazil, G. caparu n. sp., G. januari n. sp. and G. camisea n. sp. from the Amazonian region, G. mendezi n. sp., G. florezi n. sp. and G. patriceae n. sp. from northern Andes and G. gouldi n. sp. from Southern United States and central Mexico. Females of G. minuta Banks, 1898, G. gaujoni Simon, 1895 and G. gloriae (Petrunkevitch, 1930) and males of G. globosa (Petrunkevitch, 1925) and G. hirsutissima (Berland, 1935) are described for the first time. Three new combinations are proposed in congruence with the phylogenetic results: G. argyrostilba (O. P.-Cambridge, 1876) n. comb., G. dentata (Zhu & Wen, 1978) n. comb. and G. tangi (Zhu, Song & Zhang, 2003) n. comb., all previously included in Dyschiriognatha Simon, 1893. The following taxa are newly synonymized: Dyschiriognatha montana Simon, 1897, Glenognatha mira Bryant, 1945 and Glenognatha maelfaiti Baert, 1987 with Glenognatha argyrostilba (Pickard-Cambridge, 1876) and Glenognatha centralis Chamberlin, 1925 with Glenognatha minuta Banks, 1898.